Responses of source-sink manipulations on yield production and sucrose synthase activity in grains of selected rice (Oryza sativa L.) varieties - Shahruddin, Shafeeqa (2014)
The unbalanced allocation pattern of assimilate within panicle has contributed to a significant reduction in grain yield. Thus, the present research was undertaken to assess the physiological factors influencing assimilate partitioning pattern of Malaysian rice varieties. The first study was conducted for determining the genotypic variations on yield and yield components among different rice varieties, so as to identify few components limiting the rice yield. Ten Malaysian rice varieties (Sri Malaysia, Kadaria, Seberang, Pulut Siding, MR84, MR219, MR211, MR167, MR103, MR263) were grown in polybag culture under glasshouse condition. The significant correlation between grain yield and harvest index (r = 0.38*) indicated that the remobilization of assimilate from the vegetative parts of plant is critical to improve the grain yield. However, the negative correlation between grain size and the filled grain in the basal spikelet (r = - 0.43***), suggested that there was an unbalanced assimilate partitioning pattern among all ten rice varieties. Similarly, less than 100% of the filled grain resulted for all ten rice varieties. In studying the grain filling process, the second study was conducted for evaluating and elucidating the response of source-sink manipulations on; (a) the grain yield and yield components, and (b) the trend of sucrose synthase (SuS) activity in the grains among different rice varieties, respectively. Five Malaysian rice varieties (MR263, MR219, MR167, MR84, Pulut Siding) from the first study were subjected to four treatments; i.e. 50% flag leaf cutting, 25 and 50% spikelet removal, and control. Manipulations on grain number have decreased the grain yield in all five rice varieties. The 25 and 50% spikelet removal have increased the grain size of varieties MR167 and Pulut Siding, as well as the filled grain in the basal spikelet of variety MR84, thus lowering their grain yield reduction (less than 25 and 50%). The filled grain was greater in the apical spikelets, suggested that there might be an inadequate supply of assimilate to the basal spikelets. The flag leaf cutting has reduced about 9 - 14% of grain yield, as well as the filled grains (4 – 11%) in all five rice varieties. Reducing the source strength (flag leaf cutting) did not significantly affect the sucrose content in the apical and basal grains because of the compensation from other vegetative parts of the plant. The 25 and 50% spikelet removal created a situation of lower sink demand which contributed to the higher SuS activity in the apical (2 - 9%) and basal grains (3 – 21%) thereby reduced the sucrose accumulation in grains. The positive correlation between the SuS activity and sucrose content revealed that the sink strength influenced the sucrose accumulation in grains. However, the SuS activity, especially in the basal grains of varieties MR263, MR219, MR167, and Pulut Siding, was more sensitive under the adverse condition of the source-sink manipulations. Through the study, the grain yield can be increased through increased in biomass production or assimilate partitioning to the sink, which would require to study the grain filling process further. Less than 80% of filled grain for varieties MR263, MR219, MR167, and MR84 suggested that their grain yield was limited by the source strength. The significant increment of grain size and more than 80% of filled grain for variety Pulut Siding suggested that the grain yield was limited by both the source strength and sink capacity. With a limited assimilate from the source parts, the assimilate partitioning trend would be depended on the sink strength (eg. SuS activity). The lower SuS activity could be one of the reasons causing the lower starch content and higher sucrose accumulation in the basal grains.